2018
DOI: 10.1016/j.jaci.2017.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Chronic IL-33 expression predisposes to virus-induced asthma exacerbations by increasing type 2 inflammation and dampening antiviral immunity

Abstract: Anti-IL-33 or dexamethasone suppressed the magnitude of type 2 inflammation during a rhinovirus-induced acute exacerbation; however, only anti-IL-33 boosted antiviral immunity and decreased viral replication. The latter phenotype was replicated in rhinovirus-infected human AECs, suggesting that anti-IL-33 therapy has the additional benefit of enhancing host defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 57 publications
(88 reference statements)
6
58
0
Order By: Relevance
“…Girkin et al (40) reported that knockdown of IRF7 abolished RVinduced type I IFN responses in the airways in a mouse model. Werder et al (41) reported that anti-IL-33 therapy suppressed type 2 inflammation, boosted antiviral immunity, and decreased viral replication in a mouse model of virus-induced asthma exacerbations. Together, these findings highlight a mutually antagonistic role for IRF7-related antiviral immunity and IL-33-driven type 2 inflammation in driving alternative exacerbation phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Girkin et al (40) reported that knockdown of IRF7 abolished RVinduced type I IFN responses in the airways in a mouse model. Werder et al (41) reported that anti-IL-33 therapy suppressed type 2 inflammation, boosted antiviral immunity, and decreased viral replication in a mouse model of virus-induced asthma exacerbations. Together, these findings highlight a mutually antagonistic role for IRF7-related antiviral immunity and IL-33-driven type 2 inflammation in driving alternative exacerbation phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanisms may partly explain why, in the present study, IL‐33 did not directly induce the synthesis of fibronectin by murine fibroblasts in vitro , whereas per‐nasal administration of IL‐33 in vivo did enhance the expression of fibronectin in the murine airways in a manner compatible with that observed in the OVA‐challenged mice. This and other indirect effects of IL‐33 in vivo might result from its actions on cells other than fibroblasts causing the release of additional mediators, including ILC2s, macrophages and mast cells …”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic translocation of HMGB1 in AECs was quantified as described previously . Lung biopsies were stained with periodic acid‐Schiff (PAS) reagent, and mucus hypersecretion was evaluated using a semi‐quantitative scoring system as described previously …”
Section: Methodsmentioning
confidence: 99%